A Multicultural Islamic Religious Education Curriculum Development - Hamid, Noor; Wahyuni, Sri (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2024)
Curriculum development is often based on inappropriate strategies, due to a lack of comprehensive understanding of objectives, starting points, methods and functions. This study examines the development of multicultural Islamic Religious Education (PAI) curriculum in Da’wa Management Study Program (Prodi MD), Faculty of Da’wah and communication of Sunan Kalijaga State Islamic University Yogyakarta. Type of qualitative research, with the method of Case Studies (case study). The approach used is Curriculum Development. The theory used as a framework for analysis is The Theory of Grass-Roots Initiative. Research findings show that the Da’wa Management Program the faculty of Da’wa Management and communication UIN (State Islamic University) Sunan Kalijaga developed a multicultural PAI curriculum in response to the development and needs of the community. Therefore, curriculum development is centered on the field experience of the academic community, both educators and learners. The paradigm used during the development process is naturalist-inclusive, where the material, learning process, and output are directed towards one goal, namely students who are tolerant, moderate, and able to bridge social gaps, both in the classroom and in society and industry. This article contributes to providing guidance for integrating multicultural values ​​into the Islamic Religious Education curriculum, in order to create inclusive and responsive learning towards diversity.